Testing macroeconomic models by indirect inference on unfiltered data - David Meenagh; Patrick Minford; Michael Wickens (Cardiff University, Cardiff Business School, 2012)
We extend the method of indirect inference testing to data that is not filtered and so may be non-stationary. We apply the method to an open economy real business cycle model on UK data. We review the method using a Monte Carlo experiment and find that it performs accurately and has good power.
Keywords: C12; C32; C52; E1; 330; bootstrap; DSGE; VECM; indirect inference; Monte Carlo; Ökonometrisches Makromodell; Real Business Cycle; Offene Volkswirtschaft; Statistischer Test; Inferenzstatistik; Schätzung; Großbritannien